Airborne acquisition of Pneumocystis in bronchoscopy units: a hidden danger to healthcare workers. (4th October 2018) - Morilla, Ruben; Martínez-Rísquez, María T; de la Horra, Carmen; Friaza, Vicente; Martín-Juan, José; Romero, Beatriz; Conde, Manuel; Varela, José M; Calderón, Enrique J; Medrano, Francisco J
Abstract: The possible presence of Pneumocystis in a bronchoscopy unit of a tertiary-hospital was examined by detecting Pneumocystis -specific DNA by polymerase chain reaction in prospectively obtained samples of oropharyngeal wash from seven healthcare workers (HCWs) and air from three areas of the unit at different time points (baseline, days +15, +30, +60, +90 after initiation of the study). Positive samples were genotyped at two genetic loci: the mitochondrial large subunit ribosomal RNA (mtLSUrRNA) fragment by direct sequencing and the gene for dihydropteroate synthase (DHPS) by restriction fragment-length polymorphism. Pneumocystis DNA was identified in 13/24 samples from HCWs, in 4/14 air samples and also in two patients with Pneumocystis pneumonia (PcP) and another with a Pneumocystis -associated disease subjected to bronchoscopy on days +15 and +60 after initiation of the study. The HCWs harbored a high rate of mtLSU-rRNA genotypes 1 and 3 and samples from air and patients with only genotype 3. DHPS mutations related to sulpha resistance were detected in three samples from HCWs and in one from air; 65% of the positive samples showed genotypic concordance. The study demonstrates that HCWs of bronchoscopy units represent a new dynamic reservoir and a possible source of infection for human Pneumocystis species, including DHPS genotypes related to sulpha resistance that could be transmitted within hospitals to immunosuppressed hosts in whom a PcP can develop. The results provide the first evidence of the risk of Pneumocystis transmission in the bronchoscopy units and arguments to improve prevention and control of this infection in nosocomial setting.